SPDB: a specialized database and web-based analysis platform for swine pathogens. (6th August 2020) - Wang, Xiaoru; Liu, Zongbao; Li, Xiaoying; Li, Danwei; Cai, Jiayu; Yan, He
Abstract: The rapid and accurate diagnosis of swine diseases is indispensable for reducing their negative impacts on the pork industry. Next-generation sequencing (NGS) is a promising diagnostic tool for swine diseases. To support the application of NGS in the diagnosis of swine disease, we established the Swine Pathogen Database (SPDB). The SPDB represents the first comprehensive and highly specialized database and analysis platform for swine pathogens. The current version features an online genome search tool, which now contains 26 148 genomes of swine, swine pathogens and phylogenetically related species. This database offers a comprehensive bioinformatics analysis pipeline for the identification of 4403 swine pathogens and their related species in clinical samples, based on targeted 16S rRNA gene sequencing and metagenomic NGS data. The SPDB provides a powerful and user-friendly service for veterinarians and researchers to support the applications of NGS in swine disease research. Database URL : http://spdatabase.com:2080/